The Endocannabinoid System in PTSD: Molecular Targets for Modulating Fear and Anxiety - Lyndon, Stanley (Pharmacopsychiatry, 2025)
Fear and anxiety perform essential protective roles, yet when they become dysregulated, they can trap trauma survivors in persistent hypervigilance and distress. Post-traumatic stress disorder (PTSD) manifests as intrusive memories, avoidance, and heightened arousal long after the precipitating event. Although current pharmacotherapies – including selective serotonin reuptake inhibitors, adrenergic blockers, benzodiazepines, and atypical antipsychotics – provide relief for some, many patients contend with residual symptoms or intolerable adverse effects. Recent discoveries position the endocannabinoid system as a pivotal regulator of fear acquisition, consolidation, and extinction. Clinical observations of altered anandamide levels and cannabinoid receptor CB₁ upregulation in individuals with severe PTSD underscore the therapeutic potential of restoring endocannabinoid tone. Preclinical studies demonstrate that direct CB₁ agonists, fatty acid amide hydrolase (FAAH) inhibitors, and phytocannabinoids such as tetrahydrocannabinol (THC) and cannabidiol (CBD) can facilitate extinction learning and attenuate anxiety-like behaviours. Preliminary human trials report that nabilone alleviates trauma-related nightmares and that acute cannabinoid administration modulates amygdala reactivity to a threat. Yet optimal dosing strategies, sex-specific responses, and ideal THC:CBD ratios remain to be defined. Self-medication with cannabis can offer transient relief but carries a risk of cannabis use disorder and potential worsening of PTSD symptoms. By elucidating molecular targets – including CB₁, CB₂, FAAH, and monoacylglycerol lipase – this review outlines a strategic framework for next-generation cannabinoid-based interventions. Harnessing the endocannabinoid system promises to expand the therapeutic arsenal for PTSD, offering hope for more effective and better-tolerated treatments.
Keywords: posttraumatic stress disorder (PTSD); stress; anxiety disorders